Busan's Paradiplomacy: Aspiring to be the World's Premier Film City - Dermawan, Windy; Clarissa, Sarah; Affandi, RMT Nurhasan; Santoso, Rizal Budi; Jasuma, Nanda Blestri (Universitas Muhammadiyah Yogyakarta, 2023)
This study explored the image transformation of Busan, South Korea, from an industrial hub to a globally recognized City of Film. By employing a paradiplomacy framework, the research examined how Busan utilized BIFF as both a cultural event and a strategic tool for international diplomacy, economic development, and city branding. This qualitative research focused on gathering data largely through a comprehensive evaluation of scientific literature, including books and papers relevant to the case study. The analyses delved into the evolution of the BIFF event and its significant role in rebranding Busan from a declining industrial city to the first